2023
DOI: 10.1021/acs.organomet.3c00058
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Intermediates in the Synthesis of Photoluminescent Zirconium and Hafnium Complexes with Pyridine Dipyrrolide Ligands

Abstract: The two commercially available zirconium complexes tetrakis(dimethylamido)zirconium, Zr(NMe2)4, and tetrabenzylzirconium, ZrBn4, were investigated for their utility as starting materials in the synthesis of bis(pyridine dipyrrolide)zirconium photosensitizers, Zr(PDP)2. Reaction with one equivalent of the ligand precursor 2,6-bis(5-methyl-3-phenyl-1H-pyrrol-2-yl)pyridine, H2 MePDPPh, resulted in the isolation and structural characterization of the complexes (MePDPPh)Zr(NMe2)2thf and (MePDPPh)ZrBn2, which could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…After the initial discovery of long‐lived and highly quantum‐efficient photoluminescence in Zr(PDP) 2 complexes, [35] we were able to demonstrate that the emission emanates from excited states with significant ligand‐to‐metal charge transfer (LMCT) character by thermally activated delayed fluorescence (TADF) rather than phosphorescence [36] . This design principle for photoluminescent early transition metal complexes with d 0 electron configurations could also be extended to the heavier congener hafnium, resulting in Hf(PDP) 2 TADF emitters with excellent photophysical properties [37] . Further studies of the photochemical reactivity of Zr(PDP) 2 complexes revealed their utility as Earth‐abundant and cost‐efficient alternatives to precious metal photosensitizers in photoredox catalysis [35,36,38,39] and for record‐setting triplet‐triplet annihilation‐based photon upconversion at low light intensities below solar flux [40] .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…After the initial discovery of long‐lived and highly quantum‐efficient photoluminescence in Zr(PDP) 2 complexes, [35] we were able to demonstrate that the emission emanates from excited states with significant ligand‐to‐metal charge transfer (LMCT) character by thermally activated delayed fluorescence (TADF) rather than phosphorescence [36] . This design principle for photoluminescent early transition metal complexes with d 0 electron configurations could also be extended to the heavier congener hafnium, resulting in Hf(PDP) 2 TADF emitters with excellent photophysical properties [37] . Further studies of the photochemical reactivity of Zr(PDP) 2 complexes revealed their utility as Earth‐abundant and cost‐efficient alternatives to precious metal photosensitizers in photoredox catalysis [35,36,38,39] and for record‐setting triplet‐triplet annihilation‐based photon upconversion at low light intensities below solar flux [40] .…”
Section: Introductionmentioning
confidence: 96%
“…[36] This design principle for photoluminescent early transition metal complexes with d 0 electron configurations could also be extended to the heavier congener hafnium, resulting in Hf(PDP) 2 TADF emitters with excellent photophysical properties. [37] Further studies of the photochemical reactivity of Zr(PDP) 2 complexes revealed their utility as Earthabundant and cost-efficient alternatives to precious metal photosensitizers in photoredox catalysis [35,36,38,39] and for recordsetting triplet-triplet annihilation-based photon upconversion at low light intensities below solar flux. [40] Borisov and coworkers further expanded the range of applications to sensing and imaging in biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…Given the challenges noted in the attempted salt metathesis reactions for the coordination of a second pincer ligand, we proposed instead to alkylate the monoligated uranium­(IV) compound, hypothesizing that the resultant uranium–carbon bonds would serve as an internal base to drive the formation of U­( Mes PDP Ph ) 2 . Indeed, evidence supporting the need to access an organometallic intermediary complex to isolate bis-PDP compounds was shown in a recent work by some of us; a cyclometalated Zr compound, (cyclo- Mes PDP Ph )­ZrBn, was crucial to facilitate bis-ligand complex formation . The addition of 2 equiv of benzyl potassium (KCH 2 Ph) to ( Mes PDP Ph )­UCl 2 (THF) in THF at −80 °C resulted in an immediate color change from red to burgundy.…”
Section: Results and Discussionmentioning
confidence: 86%
“…Photoactive transition metal complexes based on Earth-abundant elements have become the focus of intense research over the past decade. Among them, photoluminescent early transition metal complexes displaying long-lived excited states are an emerging class of inorganic chromophores that have found application in photoredox catalysis, photon upconversion, and biological imaging and sensing. , Due to the relatively high abundance of early transition metals in the Earth’s crust, these photoactive complexes are an attractive alternative to precious metal chromophores, which have traditionally dominated the field of molecular inorganic photochemistry. While this offers the prospect of more sustainable and cost-effective photochemical applications, it also provides unique opportunities to challenge existing paradigms in photochemistry and expand the fundamental understanding of different excited state manifolds. When combined with electron-rich ligand scaffolds, the electron-poor nature of early transition metals provides ideal conditions for the generation of low energy excited states with significant ligand-to-metal charge transfer (LMCT) character, which have historically been underexplored in transition metal photochemistry and photophysics. The strong preference for d 0 electron configurations in early transition metals eliminates potentially detrimental metal-centered (MC) excited states, often resulting in remarkably long photoluminescence lifetimes of tens to hundreds of microseconds at room temperature in solution. While initial examples for d 0 LMCT luminophores relied heavily on group 3 and 4 metallocenes or group 5 imido complexes, , more recent reports introduced complexes with multiple pincer-type pyridine dipyrrolide ,, and bis­(aryloxide) N-heterocyclic carbene ligands or bidentate 2-(2′-pyridine)­pyrrolide ligands. , These ligand architectures provide increased synthetic modularity and, thereby, promise better control...…”
Section: Introductionmentioning
confidence: 99%
“… 20 22 The strong preference for d 0 electron configurations in early transition metals eliminates potentially detrimental metal-centered (MC) excited states, often resulting in remarkably long photoluminescence lifetimes of tens to hundreds of microseconds at room temperature in solution. While initial examples for d 0 LMCT luminophores relied heavily on group 3 and 4 metallocenes 23 34 or group 5 imido complexes, 35 , 36 more recent reports introduced complexes with multiple pincer-type pyridine dipyrrolide 8 11 , 14 , 37 and bis(aryloxide) N-heterocyclic carbene ligands 38 or bidentate 2-(2′-pyridine)pyrrolide ligands. 39 , 40 These ligand architectures provide increased synthetic modularity and, thereby, promise better control over the photophysical properties.…”
Section: Introductionmentioning
confidence: 99%